National Carbon Accounting – A Review on the Role of Institutional Quality on Environmental Degradation - Nuta, Alina Cristina; Tanasa, Florentin Emil (The Journal of Accounting and Management, 2023)
Climate change is a challenge for the whole world, no matter the level of social or economic development. The effects of it hinder the evolution of society and put under scrutiny human welfare. Organizations, institutions, and government worldwide state their willingness to mitigate the environmental issues and struggle to find the proper policy options to do it without affecting other priorities such as unemployment, poverty, structural gaps, and various inequalities. The study aims to briefly review the role of institutional quality on environmental degradation. The research in this field is rich and diverse covering different ways of expressing the institutional quality and its impact on ecological quality.